The Effect Of Range Of Motion (Rom) Measures On Pain In Dextra Femur Fracture Patients At Home Pematang Siantar Army Sick Year 2023 - Mangara, Azis; Perangin-angin, Riska Wani Eka Putri (Sean Institute, 2023)
Range of motion (ROM) is an exercise that moves joints and allows contraction and movement in muscles. The aim of the research is the Effect of Range of Motion (ROM) Actions on Pain in Dextra Femur Fracture Patients at the Pematang Siantar Army Hospital in 2023. The research method uses a quantitative research design with a quasi-experimental type. This research is a quasi-experimental design using a pre-test and post-test with a one group pre-test post-test design approach. The population of the study was 40 people and a sample of 36 people with inclusion criteria: the patient had a right femur fracture, willing to be a respondent. The research results showed that the p-value = 0.000 < a = 0.05, so the research hypothesis was accepted, so it could be concluded that there was an influence of Range of Motion (ROM) measures on pain in right femur fracture patients at the Pematang Siantar Army Hospital in 2023. Conclusion: pain in right femur fracture patients before being given the Rango of Motion (ROM) procedure with severe pain was 36 people (100.0%). Pain in right femur fracture patients after being given the Rango of Motion (ROM) procedure with